Thermal Performance Challenges and Mitigation Strategies for Photovoltaic Modules in High-Temperature Climates: A Case Study of Three Libyan Cities in Different Regions - Ibrahim Hadi Tawil; Zohra Ali Gebrel, (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
This study provides a comprehensive investigation into the performance of photovoltaic (PV) modules under diverse climatic conditions, emphasizing degradation induced by elevated operating temperatures. Utilizing a MATLAB-based simulation centered on a single-diode equivalent circuit model, the electrical characteristics of a standard crystalline silicon module were analyzed across three geographically distinct Libyan cities: Tripoli (temperate coastal), Sabha (hot-arid), and Kufra (high-altitude subtropical). The model integrates real-world meteorological data, including ambient temperature, solar irradiance, and wind speed, to calculate cell temperature and its impact on electrical parameters. Results quantify a significant efficiency penalty in hotter regions, driven by the module's negative temperature coefficient. This manifested as a marked reduction in maximum power point (MPP) voltage and distinct distortion of the I-V curves in desert climates compared to coastal regions. Specifically, Tripoli maintains the highest operational efficiency (above 17.5%) year-round due to its cooler climate, whereas Kufra, despite superior solar resources, experiences the lowest efficiency due to substantial thermal losses. Furthermore, the study evaluates active cooling as a thermal management intervention. The findings highlight the necessity of region-specific PV system optimization and demonstrate the efficacy of predictive computational modeling for enhancing energy yields in extreme environments.
Keywords: Photovoltaics; MATLAB; Temperature Coefficient; High-Temperature Performance; Thermal Management; Solar Energy Yield